Analyzing the core marketing functions of Debit and Credit card system of National Bank Limited - Irfan, S.M. Jian Hasan (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.